2013
DOI: 10.1007/s00430-013-0290-5
|View full text |Cite
|
Sign up to set email alerts
|

TLR4, IL10RA, and NOD2 mutation in paediatric Crohn’s disease patients: an association with Mycobacterium avium subspecies paratuberculosis and TLR4 and IL10RA expression

Abstract: Mycobacterium avium subspecies paratuberculosis (MAP) has been implicated in the pathogenesis of Crohn's disease (CD). The role of CD susceptibility genes in association with these microbes is not known. Sixty-two early onset paediatric CD patients and 46 controls with known MAP status were analysed for an association with 34 single nucleotide polymorphisms (SNPs) from 18 CD susceptibility genes. Functional studies on peripheral blood mononuclear cells (PBMCs) were conducted on 17 CD patients with known CD mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 44 publications
0
15
0
1
Order By: Relevance
“…39 Our group has previously shown that different microbes are associated with different genetic determinants, suggesting that CD may result from a combination of specific microbial and genetic factors. 40,41 Furthermore, genetic abnormalities that predispose individuals to IBD have been shown to differ substantially between the West and the East. 42 More studies that link specific microbial patterns with ethnicity and genetic abnormalities are now required.…”
Section: Discussionmentioning
confidence: 99%
“…39 Our group has previously shown that different microbes are associated with different genetic determinants, suggesting that CD may result from a combination of specific microbial and genetic factors. 40,41 Furthermore, genetic abnormalities that predispose individuals to IBD have been shown to differ substantially between the West and the East. 42 More studies that link specific microbial patterns with ethnicity and genetic abnormalities are now required.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive list of the main genetic variants in CD is summarized in Table 1. In summary, the mutational variants in CD further describe a defect in bacterial sensing, as mentioned by Wagner et al,9 and an exaggerated response of the intestinal immune system.…”
Section: Introductionmentioning
confidence: 71%
“…Currently, our genetic knowledge of CD is applied to understanding the natural history of the disease, describing racial predominance, predicting early onset stricturing and fistulizing, and determining location and overall severity of disease. Wagner et al recently described an association between mutations in toll-like receptor (TLR) 4 (rs4986790) and interleukin 10 receptor, alpha subunit (rs22291130) with Mycobacterium avium subspecies paratuberculosis positive CD patients,9 further implicating the role of microbial triggers and aberrant genetic responses in the immune system. This genetic data is helpful information that will possibly lead to the ultimate discovery of etiologies for the disease.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that both were recognised as ‘new’ entities by their distinction from tuberculosis has focused on sarcoidosis22–24 and Crohn's disease25 26 alike a search for mycobacteria as precipitants: a search which has been rewarded with findings that have identified an association without the evidence to prove it causative. From Japan, it has been reported that Propionibacterium acnes is the only microorganism to have been cultured from sarcoid lesions, persisting (like the AIEC in Crohn's disease) in a cell-wall-deficient form, which here too was found to provoke a granulomatous inflammatory reaction 27…”
Section: Discussionmentioning
confidence: 99%